1976
DOI: 10.1037/0003-066x.31.7.492
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and play: Resume and redirection.

Abstract: In an effort to stimulate and guide research on exploration and play, a brief review and outline of the concepts "exploration" and "play" is presented. A broadly conceived discussion (including various organisms, ages, and disciplines) considers future research direction. It is concluded that exploration and play behaviors lend themselves to simple observations, manipulations, experimental designs, and methods of analysis. Real understanding of these behaviors may be based on consideration of (a) a wider diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(63 citation statements)
references
References 114 publications
1
59
0
Order By: Relevance
“…Physical properties of a stimulus, such as colour, size or structural complexity, have been observed to influence the investigation of an object (Berlyne 1950;Weisler and McCall 1976;Mettke-Hofmann et al 2006). Studies like those carried out by Mettke-Hofmann et al (2006) on garden warbles have shown that birds take more time to approach and contact complex objects than to approach simple ones, which was assumed to be because individuals are influenced more by the risks associated with exploring a novel situation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Physical properties of a stimulus, such as colour, size or structural complexity, have been observed to influence the investigation of an object (Berlyne 1950;Weisler and McCall 1976;Mettke-Hofmann et al 2006). Studies like those carried out by Mettke-Hofmann et al (2006) on garden warbles have shown that birds take more time to approach and contact complex objects than to approach simple ones, which was assumed to be because individuals are influenced more by the risks associated with exploring a novel situation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Play is an intrinsically motivating and universal activity of young children and the majority of the mammalian species (Fagen, 1981;Schwartzman, 1978;Weisler & McCall, 1976). Most theorists of child development agree that early play has important effects on cognitive outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Children's play has been a continual focus of interest for educators and psychologists, and explanations of its meaning and importance abound (Weisler & McCall, 1976). One popular interpretation is that play provides opportunities to affect and control the environment in ways that the immature organism is unable to do in other contexts (e.g., Garvey, 1974;White, 1959).…”
mentioning
confidence: 99%